Acalabrutinib, venetoclax, and obinutuzumab in relapsed/refractory CLL: final efficacy and ctDNA analysis of the CLL2-BAAG trial - Fürstenau, Moritz; Giza, Adam; Weiss, Jonathan; Kleinert, Fanni; Robrecht, Sandra; Franzen, Fabian; Stumpf, Janina; Langerbeins, Petra; Al-Sawaf, Othman; Simon, Florian; Fink, Anna-Maria; Schneider, Christof; et al. (Blood, 2024)
The phase 2 CLL2-BAAG trial tested the measurable residual disease (MRD)-guided triple combination of acalabrutinib, venetoclax, and obinutuzumab after optional bendamustine debulking in 45 patients with relapsed/refractory chronic lymphocytic leukemia (CLL). MRD was measured by flow cytometry (FCM; undetectable MRD <10-4) in peripheral blood (PB) and circulating tumor DNA (ctDNA) using digital droplet polymerase chain reaction of variable-diversity-joining (VDJ) rearrangements and CLL-related mutations in plasma. The median number of previous treatments was 1 (range, 1-4); 18 patients (40%) had received a Bruton tyrosine kinase inhibitor (BTKi) and/or venetoclax before inclusion, 14 of 44 (31.8%) had TP53 aberrations, and 34 (75.6%) had unmutated immunoglobulin heavy-chain variable region genes. With a median observation time of 36.3 months and all patients off-treatment for a median of 21.9 months, uMRD <10-4 in PB was achieved in 42 of the 45 patients (93.3%) at any time point, including 17 of 18 (94.4%) previously exposed to venetoclax/BTKi and 13 of 14 (92.9%) with TP53 aberrations. The estimated 3-year progression-free and overall survival rates were 85.0% and 93.8%, respectively. Overall, 585 paired FCM/ctDNA samples were analyzed and 18 MRD recurrences (5 with and 13 without clinical progression) occurred after the end of treatment. Twelve samples were first detected by ctDNA, 3 by FCM, and 3 synchronously. In conclusion, time-limited MRD-guided acalabrutinib, venetoclax, and obinutuzumab achieved deep remissions in almost all patients with relapsed/refractory CLL. The addition of ctDNA-based analyses to FCM MRD assessment seems to improve early detection of relapses. This trial was registered at www.clinicaltrials.gov as #NCT03787264.
Gesehen am 24.02.2025